A striving for independence: a qualitative study of women living with vertebral fracture - Toss Göran; Ek Anna-Christina; Hallberg Inger; Bachrach-Lindström Margareta (BMC, 2010)
Abstract Background Quantitative studies using generic and disease-specific health-related quality of life (HRQOL) questionnaires have shown that osteoporosis-related vertebral fractures have a significant negative effect on HRQOL, but there are only few studies that address what it means to live with vertebral fracture from a deeper experiential perspective. How HRQOL and daily life are affected several years after vertebral fracture and how women cope with this are more unclear. This study aimed to describe how HRQOL and daily life had been affected in women with vertebral fracture several years after diagnosis. Methods The study design was qualitative. Semi-structured interviews were conducted with ten Swedish women during 2008. Data were analysed using qualitative inductive content analysis. Results The findings of this study revealed three themes related to the influence on HRQOL and daily life: A threatened independence, i.e. back pain, anxiety, negative impact on self-image and consequences in daily life; Strategies for maintaining independence, i.e. coping, self-care and support; and The importance of maintaining independence, i.e. the ability to perform everyday activities, social interaction and having something meaningful to do. The women were striving for independence or maintaining their independence by trying to manage different types of symptoms and consequences in different ways. Conclusion HRQOL and daily life were strongly affected in a negative way by the impact of the vertebral fracture. Information from this study may provide new knowledge and understanding of the women's experiences of living with vertebral fracture from an insider's point of view in order to obtain a deeper understanding of the women's everyday life. However, further evaluation is still needed in larger study groups.